Efficacy of a Hearing Aid Noise Reduction Function. (June 2018) - Wong, Lena L. N.; Chen, Yuan; Wang, Qianran; Kuehnel, Volker
Noise reduction systems have been implemented in hearing aids to improve signal-to-noise ratio and listening comfort. The aim of this study was to evaluate the efficacy of hearing aid noise reduction for Mandarin speakers. The results showed a significant improvement in acceptable noise levels and speech reception thresholds with noise reduction turned on. Sound quality ratings also suggested that most listeners preferred having noise reduction turned on for listening effort, listening comfort, speech clarity, and overall sound quality. These results suggest that the noise reduction system used in this study might improve sentence perception in steady-state noise, noise tolerance, and sound quality, although not all listeners preferred aggressive noise reduction. However, due to large interindividual variation, clinical application of the results should be on an individual basis.